2021
DOI: 10.1053/j.ajkd.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination in Immunoglobulin A Nephropathy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Large population-based investigations are necessary to prove causation. A single-centre study focused on IgA nephropathy found that among 89 patients with a pre-existing disease no disease flare was recorded [ 73 ]. The EMA is closely monitoring the occurrence of glomerulonephritis and nephrotic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Large population-based investigations are necessary to prove causation. A single-centre study focused on IgA nephropathy found that among 89 patients with a pre-existing disease no disease flare was recorded [ 73 ]. The EMA is closely monitoring the occurrence of glomerulonephritis and nephrotic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, among a previously reported cohort of 88 patients with known IgA nephropathy who received at least one dose of mRNA based SARS-CoV-2 vaccine, none had developed gross hematuria. 23…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, among a previously reported cohort of 88 patients with known IgA nephropathy who received at least one dose of mRNA based SARS-CoV-2 vaccine, none had developed gross hematuria. 23 Strengths of this study are the inclusion of all biopsy-proven glomerulonephritis cases diagnosed in Switzerland, which allowed to calculate true incidence rates, and the use of an unambiguous primary outcome (biopsy-proven glomerulonephritis) that limited the potential for bias. By linking the second study to the epidemiological analysis, we were able to specifically approach potential participants and achieved a considerable inclusion rate (>50% of all Swiss patients with histologically confirmed glomerulonephritis during the study period).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, leading expert opinion had empirically recommended COVID-19 vaccination for patients with immune-mediated kidney diseases [ 8 ], despite limited published data regarding vaccine efficacy in glomerulonephritides treated with immunosuppressants [ 9 ]. However, the lack of trial safety data in glomerulonephritides and reports of IgA nephropathy flares after vaccination that emerged in early 2021 [ 10 , 11 , 12 ] have led to calls for nephrologists to advocate COVID-19 vaccination but counsel patients regarding a small risk of relapsing disease for up to one month after the second dose and to monitor for symptoms suggestive of relapse [ 11 ].…”
Section: Introductionmentioning
confidence: 99%